Penetapan Nilai Rujukan Retikulosit pada Remaja Perempuan Menggunakan Sysmex XN-1000 Hematology Analyzer - Ratnaningsih, Tri; Kaslam, Surawijaya Bakhtiar; Rinastiti, Pranindya (Universitas Islam Indonesia, 2026)
Background: Iron Deficiency Anemia (IDA) remains a significant health concern among adolescent females. Reliable and effective parameters are required for the monitoring of anemia. Reticulocyte, reported as absolute reticulocyte count or reticulocyte percentage, is a valuable parameter for assessing the degree of effective erythropoiesis in anemia cases. Establishing appropriate reference values is essential for accurate interpretation of reticulocyte measurements. Objective: This study aimed to establish reference intervals for reticulocyte parameters specifically in adolescent females using the Sysmex XN-1000 hematology analyzer. Method: A peripheral blood sample was collected from female high school students aged 14-19 years who were not menstruating at the time of sampling. Blood collection was done via venipuncture into K3-EDTA tubes and further analyzed using the Sysmex XN-1000 hematology analyzer.Results: The established reference intervals were as follows: reticulocyte percentage (Ret%) 0.665–2.099%; absolute reticulocyte count (Ret#) 0.0312–0.0977 × 10⁶/µL; and reticulocyte hemoglobin (Ret-He) 26.524–32.574 pg. Data were normally distributed (p > 0.05). Reference intervals were calculated using the formula mean ± 1.96 standard deviation, with a 95% confidence level.Conclusion: This study successfully established specific reference intervals for reticulocyte parameters in adolescent females using the Sysmex XN-1000 hematology analyzer.